FOREIGN EXPERIENCE IN IMPROVING THE ORGANISATIONAL AND ECONOMIC MECHANISM FOR THE FORMATION AND DEVELOPMENT OF THE OIL AND GAS SECTOR IN THE REPUBLIC OF UZBEKISTAN (International Congress on Economics, Management and Business Studies, 2026)
This thesis examines the directions for improving the organizational and economic mechanism for the formation and development of the oil and gas sector in the Republic of Uzbekistan based on an analysis of foreign experience. Management models in Norway, the United States, and Saudi Arabia are analyzed, highlighting differences in approaches to resource rent distribution, the role of the state, and the level of market competition. The possibility of adapting specific elements of these models to the conditions of Uzbekistan is justified, taking into account the institutional characteristics of the national economy. The study concludes that enhancing transparency in revenue management, introducing innovative technologies, and implementing strategic planning for sector development are essential for sustainable growth.
Keywords: Oil and gas sector, Republic of Uzbekistan, organizational and economic mechanism, international experience, resource rent, state regulation, economic diversification.